Peningkatan Kemampuan Mengenal Huruf Melalui Media Alphabet Book Pada Kelompok A - Lukluk Jannatin Nangim; Kusumastuti Kusumastuti; Dita Primashanti Koesmadi (Early Childhood Islamic Education, 2023)
This study aims to: 1) find out how the alphabet book media can improve children's ability to recognize letters in group A at Kindergarten Dharma Wanita 2 Pelang Lor Kedunggalar; 2) to find out whether the alphabet book media can improve the ability to recognize letters in group A children at Kindergarten Dharma Wanita 2 Pelang Lor Kedunggalar. The research used was classroom action research (PTK). The object of this research is the Kindergarten of Dharma Wanita Pelanng-Lor, Ngawi. The subjects of this study were children in group A Kindergarten Darma Wanita 2 Pelang Lor Kedunggalar Ngawi, totaling 11 children consisting of 5 boys and 6 girls. The data collection techniques used were observation, interviews and documentation. The results showed that: 1) the learning process through the alphabet book media can improve the ability to recognize letters in groups in Kindergarten Dharma Wanita 2 Pelanglor. It can be seen in the activities carried out, namely in cycle 1 with the theme of plants, the sub-theme of fruit plants, the activities are children ringing letters of the alphabet, sorting letters, mentioning letter symbols. For cycle 2, the words used are longer, such as the word